2014
DOI: 10.1080/10438599.2014.924746
|View full text |Cite
|
Sign up to set email alerts
|

How enterprise strategies are related to innovation and productivity change: an empirical study of Japanese manufacturing firms

Abstract: This study analyzes the total factor productivity of 1,067 Japanese manufacturing firms. In production estimation, we employ the directional distance function and Luenberger productivity indicator. Research and development strategy survey data are used to analyze the determinant factors related to improvements in innovation and productivity. Our results indicate that increasing technology and knowledge through a "black box" process is related to an increase in productivity. Furthermore, the protection and mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Recently, Kerstens and Managi [22] and Fujii et al [23] have developed an identification method for technical innovators using productivity indicators. 2 The notion of a technical innovator has been discussed since its introduction by Färe et al [24].…”
Section: -3 Technical Innovatorsmentioning
confidence: 99%
“…Recently, Kerstens and Managi [22] and Fujii et al [23] have developed an identification method for technical innovators using productivity indicators. 2 The notion of a technical innovator has been discussed since its introduction by Färe et al [24].…”
Section: -3 Technical Innovatorsmentioning
confidence: 99%
“…Fujii et al (2015) focus on the relation between corporate productivity changes and corporate R&D strategies using productivity analysis and questionnaire data. They concluded that companies employing confidential information systems tend to increase their productivity.…”
Section: The Clarification Of Environmental Technology Was Introducedmentioning
confidence: 99%